Oocyte phenotype, genetic diagnosis, and clinical outcome in case of patients with oocyte maturation arrest - Zhu, Lixia; Yang, Qiyu; Jin, Huizi; Zhou, Juepu; Wang, Meng; Yang, Liu; Li, Zhou; Qian, Kun; Jin, Lei (Frontiers in Endocrinology, 2022)
Background: oocyte maturation arrest (OMA) is currently one of the major causes of in vitro fertilization (IVF) failure, and several gene mutations were found to be associated with OMA. The purpose of this study was to identify the oocyte phenotype, genetic diagnosis, and clinical outcomes of patients with OMA and explore their possible interrelationships, thus providing a more individualized and efficient treatment strategy guidance accordingly. Methods: A retrospective study was conducted, involving 28 infertile women with OMA in the Reproductive Medicine Center of Tongji Hospital from 2018 to 2021. Whole-exome sequencing was performed for the detection of gene mutations. Patients were classified into three groups based on their oocyte phenotype, and for each group, the immature oocytes were cultured in vitro and mature oocytes were fertilized to evaluate both the maturation capacity and developmental potential. The clinical outcomes of OMA patients with different gene mutations or from different groups were further analyzed and compared. Results: Twenty-eight women with OMA were evaluated in this study. According to the stage of OMA, 14 (50.0%) women were classified as OMA Type-1 (GV arrest), 5 (17.9%) were OMA Type-2 (MI arrest), and 9 (32.1%) were OMA Type-3 (with both GV and MI arrest). Immature oocytes from OMA patients exhibited significantly lower maturation rates even after IVM, compared to those in general patients. Seven patients (25.0%) were detected to have deleterious variations in two genes (PATL2 and TUBB8), known to be associated with the OMA phenotype. Patients with identified mutations were found to have little opportunity to obtain offspring with their own oocytes. Among the patients without mutations identified, those classified as OMA Type-1 or Type-3 still had a chance to obtain offspring through IVF or natural pregnancy, while all patients in the Type-2 group failed to obtain live birth. Conclusions: Three different phenotypes were observed in patients with OMA. The clinical outcomes of patients were associated with the presence of gene mutations and the classification of oocyte phenotype, thus a reasonable triage system was proposed to optimize the allocation of health care resources and maximize patient benefit.